Baby code! - Horning, Sandra, 1970-; Crowton, Melissa (New York , New York : Penguin Workshop, an imprint of Penguin Random House LLC, 2018)
A baby tells her dog and toys what to do just as computer code tells computers what to do, including moving a toy train, hugging her teddy bear, and taking a nap.
Cover title.
Keywords: Board books; Computer programming -- Fiction; Babies -- Fiction; Board books; Computer programming -- Fiction; Infants -- Fiction; Board books for children